Implementation of K-Means for Analysis of Factors Causing Consumer Satisfaction at Madani Hotel Medan City - Debi Masri; Adek Apriyandi; Baginda Harahap (Bulletin of Computer Science and Electrical Engineering, 2022)
Madani Hotel is one of the hotels located in Medan City which is a place of lodging for regional, national and international tourists, because this Madani Hotel is very strategically located close to the City Center, Grand Mosque, and Maimun Palace, some of which have become city icons. own field. This study uses data mining techniques using the k-means cluster method with the rapidminer application to visualize the pattern of causes of guest satisfaction with Hotel Madani both from service, facilities, comfort and price at Madani Hotel Medan City, the purpose of this research is to support and provide presentations for owners and Madani Hotel manager so that it can be used to assess how to increase the number of visits or guests at Madani Hotel Medan City. Based on research conducted, Madani Hotel's guest satisfaction score for comfort = 11, service = 14, facilities = 13, and price = 12.